Endri Juniyanto The Effect of Contributions Income, Claims Expense and Investments Return on Asset Growth in Sharia Insurance Companies (Islamic General and Life Insurance Company 2016-2020 Period) - Juniyanto, Endri; Sari , Ermina (FEB - Universitas Lampung, 2022)
This research is important to do considering the assets of the insurance company to finance the existing performance in the insurance. This research was conducted based on the statistics of Islamic insurance companies in Indonesia in the last 3 years (2016 – 2020). By using a sampling technique using purposive sampling, the final sample is 13 samples of companies with a total of 65 samples of observation. Data analysis using multiple linear regression test. The results of the study indicate that: (1) Contribution Income has a positive effect on the growth of Islamic insurance assets. (2) Claims Expense to harm the growth of Islamic insurance assets. (3) Investment Return harms the growth of Islamic insurance assets.